KEBUTUHAN RTH SEBAGAI INSTRUMEN MITIGASI PERUBAHAN IKLIM DI KOTA PALEMBANG (Studi Kasus DAS Bendung dan DAS Musi 2/Lambidaro) - Patria Primordia, Yustin; Zulkifli, Hilda; Putranto, Dinar; Iskandar, Ishkaq (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2014)
Development may result in positive or negative for human welfare Positive Negative degrade the quality of the existing environment is the main problem today is most of the space with a high value of the natural environment is degraded by the current city development process and not well controlled . Microclimate sector in the city will be greatly influenced by the condition of the green space . Management of green space in a city to be considered properly into account the contribution of green space in order to cope with the effects of global warming and climate change . This research was conducted in March 2013 by taking the location of the research on the sub region Weir River system ( East Ilir II ) and sub- systems Lambidaro River ( Gandus ) . The results of the research analysis Green Open Space Need For Climate Change Mitigation Instruments in Palembang City is currently in the year 2012 has been able to meet the needs oxygen for humans , then the city of Palembang must add an area of 12018.30 hectares of green space but the calculation results obtained by the extent of the amount of green space in Palembang 15527.88 ha of the predicted 22 % green space should exceed requirements . Palembang on lambidaro watershed currently has extensive open space : 16,595,922.667649 ha , while the area of green open space in the watershed dam of 380,193.75 ha . Based on the factors of population , building and hospitality , the minimum requirement is a green space in the city of Palembang area of 15527.88 ha so still make ends meet.